Minimal Change in Cardiac Index With Increasing PEEP in Pediatric Acute Respiratory Distress Syndrome - Virk, Manpreet K.; Hotz, Justin C.; Wong, Wendy; Khemani, Robinder G.; Newth, Christopher J. L.; Ross, Patrick A. (Frontiers in Pediatrics, 2019)
Objective: To determine if increasing positive end expiratory pressure (PEEP) leads to a change in cardiac index in children with Pediatric Acute Respiratory Distress Syndrome ranging from mild to severe. Design: Prospective interventional study. Setting: Multidisciplinary Pediatric Intensive Care Unit in a University teaching hospital. Patients: 15 intubated children (5 females, 10 males) with a median age of 72 months (IQR 4, 144) and a median weight of 19.3 kg (IQR 7.3, 57.1) with a severity of Pediatric Acute Respiratory Distress Syndrome that ranged from mild to severe with a median lung injury score of 2.3 (IQR 2.0, 2.7). Measurements: Cardiac index (CI) and stroke volume (SV) were measured on baseline ventilator settings and subsequently with a PEEP 4 cmH2O higher than baseline. Change in CI and SV from baseline values was evaluated using Wilcoxon signed rank test. Results: A total of 19 paired measurements obtained. The median baseline PEEP was 8 cmH2O (IQR 7, 10) Range 6 – 14 cmH2O. There was no significant change in cardiac index or stroke volume with change in PEEP. Baseline median CI 4.4 L/min/m2 (IQR 3.0, 4.9) and PEEP 4 higher median CI of 4.3 L/min/m2 (IQR 3.5, 4.9), p = 0.53. Baseline median SV 26 ml (IQR 10, 53) and at PEEP 4 higher median SV 34 ml (IQR 10, 48) p = 0.59. Conclusion: There is no significant change in cardiac index or stroke volume with increasing PEEP by 4cm H2O in a population of children with mild to severe PARDS. Keywords: positive end-expiratory pressure, acute respiratory distress syndrome, mechanical ventilation. Abbreviations: CaO2 = Arterial oxygen content CO = Cardiac output CI = Cardiac Index DO2 = Oxygen delivery LIS = Lung Injury Score PARDS = Pediatric Acute Respiratory Distress Syndrome Abstract word count 249 Total word count 2091